2009
DOI: 10.1016/j.stem.2009.10.015
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Interneuron Dysfunction Impairs Hippocampal Neurogenesis in Adult Apolipoprotein E4 Knockin Mice

Abstract: SUMMARY Apolipoprotein (apo) E has important and diverse functions in neurobiology, and apoE4 is the major known genetic risk factor for Alzheimer’s disease. Here we report that adult neural stem/progenitor cells (NSCs) express apoE. In apoE knockout mice, neurogenesis in the hippocampus was ~60% lower than in wildtype mice, and most newborn cells developed into astrocytes rather than into neurons as in wildtype mice. This impairment was not observed in human apoE3 knock-in mice. In apoE4 knock-in mice, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
243
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(257 citation statements)
references
References 69 publications
11
243
1
2
Order By: Relevance
“…A study more relevant to ours showed that proliferation is also increased in the hippocampus of apoE4 mice relative to apoE3 mice, whereas maturation is delayed, and overall survival is decreased (99). Taken together, these data suggest that apoE4 domain interaction modeled in the Arg-61 mice may be sufficient to cause the disruption in neurogenesis as seen in the apoE4 mice.…”
Section: Discussionsupporting
confidence: 66%
“…A study more relevant to ours showed that proliferation is also increased in the hippocampus of apoE4 mice relative to apoE3 mice, whereas maturation is delayed, and overall survival is decreased (99). Taken together, these data suggest that apoE4 domain interaction modeled in the Arg-61 mice may be sufficient to cause the disruption in neurogenesis as seen in the apoE4 mice.…”
Section: Discussionsupporting
confidence: 66%
“…Specifically, Ab modifies the balance between excitatory and inhibitory inputs on adult-born neurons (Sun et al 2009). Furthermore, risk genes for AD, such as the apolipopotein E, may have a detrimental effect on adult hippocampal neurogenesis as a result of altered signaling that promotes glial differentiation at the expense of neurogenesis (Li et al 2009). …”
Section: Adult Neurogenesis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…We previously generated and extensively characterized transgenic mice expressing enhanced green fluorescent protein (GFP) specifically within neural stem/progenitor cells (NSPCs) under the control of the neural progenitor-specific form of the nestin promoter and enhancer (Chen et al, 2009;Gritti and Bonfanti, 2007;Li et al, 2009;Li et al, 2008;Miles and Kernie, 2008;Shi et al, 2007;Yu et al, 2005;Yu et al, 2008). In addition, we recently demonstrated that ApoE expression increases dramatically from postnatal day (P) 7 to one month of age in GFP-expressing neural progenitor cells within the subgranular zone of the dentate gyrus (Gilley et al, 2011).…”
Section: Apoe Expression Is Specific To Early Neural Stem/progenitorsmentioning
confidence: 99%
“…ApoE has long been implicated in a variety of neurodegenerative processes that affect hippocampal function. Recent data demonstrate that it also has dentate gyrusspecific effects, including directing progenitor fate towards astrocytic lineages (Bu, 2009;Li et al, 2009). This present work demonstrates that ApoE actually plays a dual role in dentate gyrus development.…”
Section: Research Article Apoe Regulates Adult Neurogenesismentioning
confidence: 99%